(untitled) (Update Dental College Journal, 2013)
The study was conducted to evaluate the quality of alginate impression sent to commercial dental laboratories for fabrication of Fixed partial dentures (FPD), to describe the frequency of clinically detectable errors and to determine correlation between factors. A Cross-sectional Study in eight commercial dental laboratories was conducted and a sample of 171 impressions was examined. For each impression, type of tray used, number of prepared units per jaw, model preparation time, manipulation quality, impression of arch, tray showing through impression material and utilization of embedded retraction cord were recorded. Over half of the specimens (58%) inspected were found to be unsatisfactory as they contained at least one detectable error. These errors included alginate manipulation with granularity (5.8%), Impression of partial arch (26.3%), Bubbles at finish line (4.1%) Presence of tears along the margin (6.4%), Tray showing through material (43.9%), Delayed model prepared (29.8%) and Did not used Retraction cord (78.4%). Significant associations were found between manipulation of impression material and presence of tearing at the margin line ( p=.007) and presence of bubbles at the margin line (p=.011). Selecting alginate impression material as a final impression is not a good choice for fabricating FPD. Therefore, the dental practitioners need to revise their treatment plan before taking impression. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13950 Update Dent. Coll. j: 2012; 2 (1): 02-07